Computational Investigation into the Enzyme-Catalyzed [4+2] Cycloaddition of Decatromicin (Communications in Computational Chemistry, 2025)
This study presents a detailed examinationof enzyme-catalyzed pericyclic reactions, specificallyfocusing on the synthesis of spirotetronate (decatromicin),catalyzed by the Plol4 enzyme. Utilizing the QM/MMmethod, we have discovered that the Plol4 enzymesignificantly reduces the energy barrier in the Diels-Alder (DA) reaction, demonstrating its effectiveness infacilitating complex chemical processes. Our analysissuggests that this reduction is partly due to the interactionbetween the substrate and active site residues within theenzyme, which prearranges the substrate in a manner conducive to the [4+2] cycloaddition. Moreover, we observed a notableshift in the DA reaction mechanism from a concerted approach within the gas phase to an asynchronous approach within theenzymatic environment. This finding highlights the unique role of Plol4 in altering reaction pathways and underscores theenzyme's potential in synthetic applications. Overall, this research provides valuable insights into the mechanisms of enzyme-catalyzed reactions and their implications for the synthesis of polycyclic compounds.